Biofilm formation during wastewater treatment: Motility and physiological response of aerobic denitrifying bacteria under ammonia stress based on surface plasmon resonance imaging. (October 2022) - Weng, Xun; Mao, Zheng; Fu, Hui-Min; Chen, You-Peng; Guo, Jin-Song; Fang, Fang; Xu, Xiao-Wei; Yan, Peng
Graphical abstract: Highlights: The motility of aerobic denitrifying bacteria was investigated by an SPR imaging. SPRI-based bacterial interface motion parameters revealed its metabolic states. Rotational and vertical movements of the bacteria were inhibited by ammonia stress. Biofilm formation was enhanced by reducing movement and promoting EPS secretion. Bacterial secretion and lipopolysaccharide synthesis of genes were up-regulated. Abstract: A bacterial image analysis system based on surface plasmon resonance imaging was established to investigate the effect of bacterial motility on biofilm formation under high ammonia nitrogen at the single-cell level. The results showed that the bacterial mean rotation speed and vertical motility distance decreased with the increasing concentration of ammonia nitrogen. Ammonia nitrogen inhibited the metabolic activity of the bacteria, decreasing bacterial motility. Bacterial motility was negatively correlated with the biofilm-formation ability. The biofilm formation ability of Enterobacter cloacae strain HNR exposed to ammonia nitrogen was enhanced by reducing its movement and promoting EPS secretion. Genes related to the tricarboxylic acid cycle and oxidative phosphorylation were down-regulated, indicating inhibition of microbial energy metabolism. Genes related to bacterial secretion and lipopolysaccharide synthesis were up-regulated, facilitating the formation of biofilms and enabling the bacteria to resist ammonia nitrogen stress. This study provides new insights into the biofilm formation under ammonia stress.